Sosialisasi Mencegah Judi Dan Pinjaman Online Di Masyarakat Pekon Yogyakarta Selatan - martin, Afrizal martin; Widianto, Widianto; Mardiyanto, Mardiyanto; Joni, Joni; Andriyani, Novita (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
The socialization activity with the theme "Preventing Gambling and Online Loans in the Pekon Yogyakarta Selatan Community" aims to increase public awareness of the dangers of gambling and illegal online loans that are rampant. Gambling and illegal online loans not only have a detrimental economic impact, but also have the potential to cause serious social problems, such as family conflict, involvement in illegal activities, and psychological pressure on the perpetrators and their families. This activity was carried out through direct counseling involving community leaders, village officials, and participants from various community groups. The material presented included the dangers of gambling, characteristics of illegal online loans, and preventive measures that can be taken by the community. The results of the activity showed an increase in public understanding of the risks and negative impacts of both problems, as well as greater motivation to stay away from these detrimental activities. Participants were also given practical information on how to recognize illegal online loans and strategies for reporting gambling activities to the authorities. This activity is expected to create collective awareness in the Pekon Yogyakarta Selatan community to create a safer environment, free from gambling practices and illegal online loan traps.